The Effectiveness of Using Team Pair Solo Strategy in Teaching Writing Descriptive Text for the Second Grade Students in SMPN 2 Peterongan - Santi Purwanti; Ima Chusnul Chotimah (SELL Journal : Scope of English Language Teaching, Linguistics, and Literature, 2017)
The purpose of conducting this research was to investigate the effectiveness of using Team Pair Solo Strategy in teaching writing descriptive text for the second-grade students in SMPN 2 Peterongan. Team Pair Solo Strategy is kind of cooperative learning strategy where the students do a task in group, in pair, and individually. The subjects of this research were 8-A and 8-B which consist of 32 students. Pre-test and post-test were given to both of experimental and control class. For the treatments, the students of experimental class were taught by using Team Pair Solo Strategy. In contrast, the students of control class were taught by Conventional Strategy. Post-test was given after giving the treatments. The result showed that F value was 4.955 than F table was 3.99. It was clearly shown that F value was higher than the F table (4.955>3.99). It means that Ha was accepted. Based on the proven hypotheses, the researcher can conclude that the using of Team Pair Solo Strategy in teaching writing descriptive text for the second-grade students in SMPN 2 Peterongan was proven effective.